Neuroendocrine Tumour as a Diagnostic and Prognostic Criterion for Autoimmune Gastritis - S. I. Mozgovoi; M. A. Livzan; T. S. Krolevets; A. G. Shimanskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To describe modern approaches to the diagnosis and treatment of neuroendocrine gastric tumours associated with chronic autoimmune gastritis on the example of a clinical case.General provisions. Patient H., born in 1948, suffered from a dyspepsia syndrome, the presence of chronic exhelicobacter gastritis and neuroendocrine tumour of unclear histogenesis in the upper third of the stomach body. The patient also suffered from systemic lupus erythematosus with skin lesions (discoid rash, palmar and plantar capillaries) and joint lesions (migrating polyarthritis). A general clinical examination revealed mild chronic iron deficiency anemia and increased neuron-specific enolase (NSE). An EGDS examination using expert-class equipment with the NBI function of close focus identified subepithelial formations of the stomach body. The histological results showed a morphological pattern consistent with a highly differentiated neuroendocrine tumour (G1), type 1, associated with chronic autoimmune gastritis.Conclusion. The autoimmune genesis of the chronic inflammation of the gastric mucosa may serve as a background for the development of neuroendocrine tumours of the stomach, which determines the management tactics in such conditions.